Human Resources Development Practices: Case Study in Indonesian Vocational High School - Rosana, Dina Syarifah; Roesminingsih, Erny; Hariastuti, Retno Tri (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Human resources in schools must be appropriately managed, including through development activities. The primary goal of human resource development is to enhance traits that contribute to higher work productivity. This research discusses about the importance of human resource management in school management as one of the keys to educational success. Therefore, good human resource management is needed, one of which is through development activities. The role of human resource development is to improve quality which has an impact on work productivity. This research aims to explore human resource development practices in one of the vocational high schools in Indonesia. The research method used is qualitative research with a case study design to describe human resource development practices at SMK SORE Tulungagung. In this research, data collection was carried out through observation, interviews and documentation to obtain in-depth information regarding human resource development practices at the school. The data obtained was then analyzed using a qualitative descriptive approach. The research results show that the development of human resources at SMK SORE Tulungagung is carried out in two ways, namely internal training and external training. Human resource development is also carried out through several stages, namely planning, implementation and evaluation. The conclusion of this research is that human resource development practices at SORE Vocational School can be an example for other schools in implementing human resource development practices in vocational schools.